An Exploration of Death Cafés in Canada - Karrel, Miriam (My University, 2018)
Do people talk about death? Many scholars argue that people in our society do not talk about death; that it is taboo, it is denied or sequestered into hospitals and funeral homes and exists outside of everyday life. And yet, others argue that death is “a very badly kept secret” with hundreds of books published on the topic in the last few decades, most of them claiming that we cannot talk about death. This disconnect leads some to argue that there is a revival of death happening instead. My research sits at the nexus of this tension; I attended death cafés around Southern Ontario to explore the dialogues that emerge in spaces set out to break the presumed taboo around death. At a death café people are meant to “drink tea, eat cake, and talk about death.” The objective of these events is “to increase awareness of death with a view to helping people make the most of their finite lives.” This statement, from the official death café website, assumes that facing death will help to make sense of, and give perspective to, life. I explore how and if death cafés accomplish their intended purpose of encouraging existential discussion, and if such a discussion was in fact beneficial to the attendees. I argue that the discussions at the death cafés I attended did not seem to fulfill the purpose stated on the website of encouraging existential discussion about one’s own death. I then situate this observation in the context of broader understandings of the denial of death thesis generally and in terms of residual Victorian romanticism and attachment to others.
Keywords: Anthropology, death